Synthesis and antimalarial activity of novel bicyclic and tricyclic aza-peroxides. Issue 28 (1st March 2016) - Yadav, Lalit; Tiwari, Mohit K.; Kumar Shyamlal, Bharti Rajesh; Mathur, Manas; Swami, Ajit K.; Puri, Sunil K.; Naikade, Niraj K.; Chaudhary, Sandeep
Abstract : Bicyclic and tricyclic aza-peroxides were synthesized and assessed for their in vitro and in vivo antimalarial activities against Plasmodium falciparum (3D7 strain) and Plasmodium yoelii nigeriensis in Swiss mice by an oral route, respectively. Abstract : For the first time, novel bicyclic5a–h as well as tricyclic9a–h aza-peroxides were synthesized using a 1 O2 -mediated photo-oxygenation methodology as a key step in 52–71% yields in which one of the oxygen atoms of the 1, 2, 4-trioxane ring has been replaced by a nitrogen atom. The methodology is simple and is an efficient way to access 1, 2-dioxa-4-aza six membered ring compounds. All these compounds were assessed for their in vitro antimalarial activity against Plasmodium falciparum . Compound9a, 9c and9f, the most active compound of the series, showed IC50 values of 9.43, 8.83 and 5.63 ng mL −1, respectively which were found to be comparable to that of the antimalarial drug chloroquine (IC50 value 5.2 ng mL −1 ). Compound9f, the most active compound found in in vitro studies, provided 40% protection to infected mice at the dose of 96 mg kg −1 × 4 days when screened for its antimalarial activity in vivo against multidrug-resistant Plasmodium yoelii nigeriensis in Swiss mice by the oral route. In this assay, β-arteether and chloroquine, showed 100% suppression of parasitaemia on day 4 and provided 100% and 80% protection, respectively, to the infected mice.